2016
DOI: 10.1002/eat.22606
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity‐related traits distinguish women with co‐occurring bulimia nervosa in a psychiatric sample

Abstract: Impulsivity-related traits of negative urgency and lack of premeditation significantly differentiated women with versus without co-occurring BN among women with borderline personality disorder. Lower levels of impulsivity-related traits in women with MDD indicated that effects were not simply attributable to any form of psychopathology. Of the impulsivity traits, negative urgency demonstrated the strongest effect, providing further evidence of the important relationship between negative urgency and the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…BPD presents alongside BN/BSD in approximately 35% of cases [5]. As these conditions are often comorbid they share many of the same risk factors, phenotypes, and behavioural traits including: attachment disturbances [6], adverse childhood experiences [7], non-suicidal self-injury [8], interpersonal difficulties [4, 9], and comorbid maladaptive mood and impulse regulation behaviours [10, 11]. In lieu of the large degree to which BPD interferes with interpersonal functioning, sense of self, and quality of life, it can be hypothesized that the 35% of those with BN/BSD and comorbid BPD (BN/BSD-BPD) face unique challenges.…”
Section: Introductionmentioning
confidence: 99%
“…BPD presents alongside BN/BSD in approximately 35% of cases [5]. As these conditions are often comorbid they share many of the same risk factors, phenotypes, and behavioural traits including: attachment disturbances [6], adverse childhood experiences [7], non-suicidal self-injury [8], interpersonal difficulties [4, 9], and comorbid maladaptive mood and impulse regulation behaviours [10, 11]. In lieu of the large degree to which BPD interferes with interpersonal functioning, sense of self, and quality of life, it can be hypothesized that the 35% of those with BN/BSD and comorbid BPD (BN/BSD-BPD) face unique challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Impulsivity contributes to dysfunctional behaviors such as eating disorders, Attention Deficit and Hyperactivity Disorder, psychopathy, poor job performance (O'Connor & Jackson, 2008), risky sexual behavior (Charnigo et al, 2013;Netto et al, 2016). The people with some diseases typically tend to be more impulsive (Ahn & Vassileva, 2016;Dervic et al, 2015;Evren & Bozkurt, 2017;Maraz et al, 2016;Netto et al, 2016;Reas et al, 2016;Steele et al, 2017;Tamam et al, 2017;Zhao et al, 2017), but not always. For example, low impulsivity characterizes people with oncological diseases (Manova, 2014).…”
Section: Psychological Thoughtmentioning
confidence: 99%
“…Impulsivity is not a unitary construct (Adams et al, 2012;Maraz et al, 2016), but it is a multifaceted (Evren & Bozkurt, 2017;Maccalum et al, 2007;Netto et al, 2016), multidimensional (Adams et al, 2012;Maccalum et al, 2007;Magid et al, 2007;Ramakrishnan et al, 2019), complex (Magid et al, 2007), heterogeneous (Dick et al, 2010) construct. Impulsivity is characterized by rapid, unpredictable, unplanned, spontaneous, rashly and sudden reactions to stimuli (Adams et al, 2012;Chase et al, 2017;Dick et al, 2010;Maccalum et al, 2007;Pérez Fuentes et al, 2016;Ramakrishnan et al, 2019), rapid decision-making and action (Magid et al, 2007;Patton et al, 1995), before complete processing of information, without considering all the information available (Maccalum et al, 2007;Molero Jurado et al, 2020;Pérez Fuentes et al, 2016), without adequate forethought, deliberation, premeditation or planning (Adams et al, 2012;Charnigo et al, 2013;Chase et al, 2017;Daurio et al, 2018;Dick et al, 2010;Gunn et al, 2018;Harden & Tucker-Drob, 2011;Johansen, 2014;Lynam, n.d.;Maccalum et al, 2007;Magid et al, 2007;Merchán-Clavellino et al, 2020;Molero Jurado et al, 2020;Patton et al, 1995;Ramakrishnan et al, 2019;Reas et al, 2016;…”
Section: Definitions Of Impulsivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies testing this hypothesis have not yet been reported in humans and will be needed to confirm this hypothesis. Alternatively, several studies have found that elevated rates of impulsivity and behavioral disinhibition contribute to binge-eating episodes in patients with BN and BED [2][3][4][5][6]. Psychopharmacologic studies support a role for fluoxetine and lisdexamfetamine in treating…”
Section: Introductionmentioning
confidence: 99%